Occupational exposure to amorphous silica dust and pulmonary function. Issue 11 (November 1990) - Choudat, D; Frisch, C; Barrat, G; el Kholti, A; Conso, F
Abstract : Respiratory manifestations among 41 workers exposed to amorphous silica dust were compared with a control group comprising 90 workers of equivalent socioeconomic state in the same plant. Flow volumes were determined, blood gas concentrations were measured at rest and during exercise, chest radiographs were obtained, and data about respiratory symptoms were collected by questionnaire. A dust exposure index was calculated for each exposed worker. It was not possible to differentiate between the two groups from the questionnaire, blood gas analysis, or chest radiographs. On the other hand, the tests of respiratory function showed a significant decrease in forced expiratory flow (FEF25-75, FEF50, and FEF75) in the exposed group compared with the controls, although no correlation was found between the exposure index and pulmonary function. It appears that smoking and exposure to amorphous silica synergise to induce small airway disease.